Analysis of Brain Tumors Due to the Usage of Mobile Phones - Saeed, Soobia; Shaikh, Asadaullah; Noor, Shabaz Ahmed (Mehran University Research Journal of Engineering and Technology; Vol 36 No 3 (2017): July Issue, 2017)
The impact of cellular phone radiation on human health is the subject of current mindfulness and is an outcome of the huge increase in phone usage throughout the world. Phones use electromagnetic radiation in the microwave range. The issue is associated with wireless use for 50 minutes and above. The excessive use of mobile phone may cause brain tumors. Nowadays the most commonly developed brain tumor type is GBM (Glioblastoma) in multiform and Malignant Astrocytoma. In this paper, we focus on the causes of brain tumor (cancer) due to the cell phone as this increase in glucose metabolism. The aim of the study is to address the aforementioned problems associated with the cell phone. MATLAB programming to detect a brain tumor has been used. We have conducted MRI (Magnetic Resonance Imaging) study to get the best images and results.